(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
The adsorption of 2, 4-dichlorophenol (2, 4-DCP) from aqueous solution on ferric oxide was carried out in a batch process. The experiments were done to determine the equilibrium time of adsorption, effect of temperature, pH, electrolytes and substituted groups of adsorbate to elucidate the mechanism of the adsorption. The estimated equilibrium time was found to be three hours. The adsorption was found to increase with increasing temperature from 30 - 50ºC. The numerical values of differential heat of adsorption increased with increasing surface coverage suggesting that the adsorption on ferric oxide might be chemical in nature. The adsorption of 2, 4-DCP on ferric oxide was found to increase with increasing pH of the solution from 3.0 - 5.0 but further increase of solution pH from 5.0 - 8.0 decreased the adsorption. Electrolytic effect showed that the adsorption was favorable in presence of NO3- ion as compared with Cl- ion. The effect of substituted groups showed that the amount of 2, 4-DCP adsorbed on ferric oxide was lower than that of 2, 5-DCP. Such observations suggest that the adsorption of 2, 4-DCP on Fe2O3 is dominated by the electrostatic force of attraction between DPC ions and iron oxide surface in aqueous media. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15674 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 1-10, 2013